2021
DOI: 10.1021/acsaem.1c01086
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fuel Cell Performance Using Ultrafast, Out-of-Plane Proton-Conducting, 3D Graphene Oxide as an Electrolyte

Abstract: Despite the considerable in-plane proton conductivity of graphene oxide (GO) nanosheets, inadequate single-cell performance in a polymer exchange membrane fuel cell (PEMFC) occurred on incorporating a vacuum-filtration-prepared GO membrane between the electrodes. In particular, the proton transfer between the electrodes in the PEMFC single cell is in the out-of-plane direction of the GO membrane and was found to be significantly lower than for the in-plane direction due to the presence of proton conduction bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Very recently, the freeze-dried route-driven 3D GO was found to show significantly higher proton conductivity compared to the traditional vacuum dried 2D GO. 29 Herein, we also observed that the freeze-drying process of oxidized SWCNT can improve the proton conductivity over Ox-SWCNT-OD. The probable cause is explained in ESI.…”
Section: Resultsmentioning
confidence: 53%
“…Very recently, the freeze-dried route-driven 3D GO was found to show significantly higher proton conductivity compared to the traditional vacuum dried 2D GO. 29 Herein, we also observed that the freeze-drying process of oxidized SWCNT can improve the proton conductivity over Ox-SWCNT-OD. The probable cause is explained in ESI.…”
Section: Resultsmentioning
confidence: 53%
“…The maximum power density obtained using 3DGO-CNTOX1 is the highest literature value so far reported for a GO-based PEMFC and even higher than that obtained for a Nafion based PEMFC under identical experimental conditions (see Table S2). [31,45,46,49,50]…”
Section: Comparison With Previously Reported Workmentioning
confidence: 99%
“…[30] Furthermore, the application of the simple and efficient freeze-drying synthetic procedure promotes the formation of numerous pores and ion transport nanochannels. [31] Nevertheless, the resulting higher porosity weakens the structural integrity giving rise to lower mechanical strength in conjunction with an increase in the number of non-connected ion conduction channels. [32] Clearly, for optimum application as electrolyte in a PEMFC, sequentiallyarranged, multiple proton-conduction channels, with short pathways are required.…”
Section: Introductionmentioning
confidence: 99%
“…[24] To circumnavigate this, the use of 3D graphene oxide (3DGO) appeared highly attractive since it has a highly porous structure and thus provides numerous channels for the propagation of protons in different directions while resulting in the mean proton conduction pathway being significantly shortened. [41] However, maintaining the high performance of a PEMFC, especially under higher temperature and lower humidity conditions, while also ensuring a long lifetime, is exceedingly challenging. In a further approach, PEMFC efficiency has been demonstrated to be enhanced by incorporation of a dopant containing both hydrophilic and hydrophobic domains, as occurs in aromatic sulfonic acids (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%